Inovasi Manajemen Pelayanan Publik Melalui Government Resources Management System (GRMS) di Provinsi Jawa Tengah - Huda, Muhammad Nurul (JPW (Jurnal Politik Walisongo), 2020)
Innovation is a necessity that must be done in the era of disruption, both private and government organizations. The Government of Central Java Province was the first province to implement an innovative GRMS (Government Resources Management System) system in the government management and public service sectors. The purpose of this study was to analyze the use of the application system, how the development was needed and the obstacles found. This study was a descriptive and used qualitative approach. Primary data was from system users, and secondary data was from the application system used. The presence of the GRMS application system directly forced regional apparatuses to adapt using digital systems, then the old bureaucratic patterns which were conventional and slow are now transforming into digital-based fast, easy, and transparent bureaucracy, so that it is expected to create good public service management.